Optical and dielectric properties of PbZrO3 thin films prepared by a sol–gel process for energy-storage application. (15th January 2016) - Zhang, T.F.; Tang, X.G.; Liu, Q.X.; Jiang, Y.P.; Jiang, L.L.; Luo, L.
Abstract: PbZrO3 thin films with (100) and (111) orientation were prepared by a simple sol–gel method. X-ray diffraction results revealed that post-annealing temperatures played an important role on the orientation of PbZrO3 films. The frequency dependence of dielectric properties and the ferroelectric characteristics were measured. Giant energy-storage density and energy-storage efficiency calculated from hysteresis loops achieved about 25.25 J/cm 3 and 62% for PbZrO3 film with thickness of 292 nm, respectively, results indicated that PbZrO3 thin films had a potential application in energy-storage device. Optical properties of PbZrO3 thin films were analyzed by a spectroscopic ellipsometer, results revealed that (111)-orientated PbZrO3 thin films exhibited higher refractive index than that of the (100)-orientated PbZrO3 thin films. Graphical abstract: Highlights: PbZrO3 thin films were prepared by a simple sol–gel method. Post-annealing temperature played an impact on the orientation of PbZrO3 films. Energy-storage density achieved from hysteresis loops achieved about 25.25 J/cm 3 . (111)-orientated PbZrO3 films exhibited higher refractive index.